Keratin 17 in psoriasis: Current understanding and future perspectives. (August 2022) - Lin, Yiting; Zhang, Weigang; Li, Bing; Wang, Gang
Abstract: Keratin 17 (K17) is a multifaceted cytoskeletal protein that is not commonly expressed in the epidermis under normal physiological conditions. However, in psoriasis, K17 is overexpressed in the suprabasal layer of the epidermis and plays an important role in the pathogenesis of the disease. In this review, we have summarized our findings and those reported in other studies concerning the pathogenic functions of K17, as well as the mechanisms underlying the increase in K17 expression in psoriasis. K17 exerts both pro-proliferative and pro-inflammatory effects on keratinocytes. Moreover, K17 peptides trigger autoreactive T cells and promote psoriasis-related cytokine production. In turn, these cytokines modulate the expression, stability, and protein–protein interactions of K17 through transcriptional and translational regulation and post-translational modification of K17 in keratinocytes. Thus, a K17/T-cell/cytokine autoimmune loop is implicated in the pathogenesis of psoriasis, which is supported by the fact that therapies targeting K17 have achieved good outcomes in psoriasis-like mouse models. Future perspectives of K17 in psoriasis have also been discussed to provide potential directions for further studies. Highlights: K17 exerts pro-proliferative and proinflammatory effects on keratinocytes. A K17/T cell/cytokine autoimmune loop is implicated in psoriasis pathogenesis. K17 can potentially serve as a therapeutic target in psoriasis treatment.